Influence of fuel ashes on corrosion of surface coatings cladded by CMT method. Issue 4 (16th February 2019) - Dębowska, Aleksandra; Magdziarz, Aneta; Kopia, Agnieszka; Kalemba–Rec, Izabela; Petrzak, Paweł
ABSTRACT: The aim of the present research was to investigate the influence of different biomasses and sewage sludge ash (at 650°C for 1000 h and 2000 h, respectively) on the surface of weld cladded (Cold Metal Transfer technique, CMT) stainless steels 309 and 310. The biomass ashes were rich in K2 O, CaO, SiO2, whereas sewage sludge ash in P2 O5, CaO, Fe2 O3, and SiO2 . Characterization of the stainless steel cross-section and surface after the corrosion process inducted by the presence of ash were carried out by scanning electron microscopy (SEM) with EDAX analysis. Phase analysis of corrosion products was made by X-ray diffraction (XRD). Chromium, nickel, and iron oxides were the main oxides which occurred after the corrosion test. It has been proved that biomass ashes have the corrosive properties (because of their chemical composition) and are more aggressive than the sewage sludge ash for that kind of materials.